UPAYA MENINGKATKAN MINAT SISWA TERHADAP LAYANAN INFORMASI BIMBINGAN DAN KONSELING MATERI PENGARUH PERGAULAN REMAJA MELALUI MEDIA AUDIO VISUAL PADA KELAS VII SMPN 1 STM HULU SEMESTER 1 TAHUN PELAJARAN 2017/2018 - Longser Gultom (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
This research is a Classroom Action Research (PTK) with the research subjects of all students in class VII SMPN 1 STM Hulu, totaling 33 students. Data collection was carried out by several methods, including: observation, tests and documentation. The data validation used triangulation techniques. Analysis of the data used in this study using qualitative descriptive analysis, which is a research procedure that uses descriptive data in the form of written or spoken words. The research activities carried out are planning action, action, observation and reflection. The result of this research is the use of audiovisual media in BK services, the influence of socialization between class VII students of SMPN 1 STM Hulu, this is indicated by an increase in the ability of students' interest in learning per cycle where in the initial conditions only 12 students or 38.71%, cycle I there were 18 students or 58.06%, and in cycle II there were 28 students or 90.32%, this result was in accordance with the determined indicators, namely the good and very good categories which reached 85%. From the explanation above, it can be concluded that the use of audiovisual media in BK services on the influence of adolescent socialization is proven to be able to increase student interest in class VII SMPN 1 STM Hulu semester 1 of the 2017/2018 school year